DETERMINAN STRUKTUR MODAL PADA PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rusanti, Rosalia; Andarwati, Andarwati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The contribution of agriculture companies to Indonesia’s economic growth is quite significant. Therefore, agriculture companies have an important role and need to be considered. One of the efforts to encourage agriculture companies to develop more is by defining their capital structure. By understanding the determinants of capital structure, agriculture companies can make the right decisions to ensure funding for the sustainability of their operational activities. This study aims to analyze the effect of firm size, profitability, sales growth, liquidity and asset structure on the capital structure of agriculture companies listed on the Indonesia Stock Exchange for the period of 2013-2019. In this study, the unit of analysis was 70 samples. Hypothesis testing was carried out using multiple linear regression analysis method. The results of this study revealed that the firm size variable has no effect on the capital structure. Meanwhile, the variables of profitability, liquidity and asset structure have a negative and significant effect on capital structure and sales growth variables have a positive and significant effect on capital structure.